Antibacterial Efficacy of the Phyto-Fabricated Chitosan and Chitosan-Based Silver Nanoparticles against Acinetobacter Baumannii Isolates Antibacterial Resistance - Irayyif, Sajjad Mohsin (American Journal of Biomedicine and Pharmacy, 2025)
Background and Aim: Healthcare-associated infections are caused by Acinetobacter baumannii. Despite being an opportunistic disease, A. baumannii infections are famously challenging to treat because of acquired and innate antibiotic resistance, which frequently restricts the range of feasible treatment choices. In the medical setting, A. baumannii can persist for extended periods of time, especially on inanimate surfaces. In order to compare the use of chitosan (ChNPs), silver nitrate (AgNPs), and phytofabricated chitosan-based silver nitrate (GNPs) nanoparticles in the medical field, this study was conducted. Methods: The methanolic flower extract of Spathodea campulata was used to create the nanoparticles in an environmentally friendly manner. FTIR, SEM, NTA, and UV-visible spectroscopy were used to characterize the produced nanoparticles. Antibacterial activities of the NPs were demonstrated against isolates of Acinetobacter baumannii in vitro by using well diffusion, MIC, MBC, ROS generation test, COMET assay, and qPCR. Results: According to our data, the different absorption ranges for the nanoparticles were as follows: AgNPs, CHNPs, and GNPs displayed absorption peaks at 345 nm, 320 nm, and 482 nm, respectively. The average size of the synthesized NPs, as determined by the SEM examination, was 76 nm for ChNPs, 90 nm for AgNPs, and 65 nm for GNPs. According to the broth dilution assay, the MIC for GNPs and the positive control was 48.3μg/ml and 25.6μg/ml, respectively. The MBC values for GNPs and the positive control were 23.4 μg/ml and 6.8 μg/ml, respectively. Following treatment with AgNPs at both concentrations, ROS production significantly increased in comparison to the control and positive control (P<0.05). A clear pattern of DNA damage was evident in the generated NPs at ½ MIC concentration (P<0.05). Based on the relative expression data, we discovered that all three members of the outer membrane protein gene (OmpA, Omp33, and OmpW) had dramatically decreased expression after treatment (P<0.05). This study shows that the produced nanoparticle has the potential to be a strong antimicrobial agent.